Symbolism of Punjab in Sufi poetry: A Study of the Works of Shāh Hussain (Al-Qamar, 2020)
The diction of metaphysics is a deep-rooted notation for poets around the globe. Different poets had used physical and non-physical symbols and metaphors in their poetry and writings. This research article revolves around the objects, which are a part of rich Punjabi culture as a sensation of metaphysical symbols and similes for Punjabi poets that illustrate the philosophy of life. These symbols and similes can easily be conversed in the poetry of the Sufi saint of Punjab Shāh Hussain (1539-1599), generally known as Mādhū Lāl Hussian or Shāh Fakīr. This paper designates the symbolic meaning of spinning and spinning wheel Charkha, the material (fibers and yarns) Sūt, for spinning and the results of this activity (the thread) tār, Warp and weft tānā bānā and the process of weaving as a result of qualitative analysis. In this regard, poetry of Shāh Hussain reflects the true sense of asceticism with material symbols of Punjab. Concerning the records of beliefs from different sources and treaties in Punjabi culture, this paper also gives a comparative study with fundamental aspects of  human reality, birth, fate and the evolution between the world of the living and that of the dead by fading one’s identity.
Keywords: Punjab; symbolism; Sufi poetry; Shāh Hussain; Charkha; Sūt; tānā bānā